Avaliação do bandeamento cromossômico por digestão enzimática e tratamento com solução tampão citratado - Rossetto, Cristina Ferreira Ramos [UNESP] (2015)
Human Cytogenetics is the study of chromosomes, their structure and their inheritance, applied to the practice of medical genetics. For nearly fifty years the chromosomal abnormalities, microscopically visible changes in the number and / or structure of chromosomes, may be responsible for a number of clinical conditions known as chromosomal aberrations, which are a category of constitutional or acquired genetic diseases. Several amendments were described in genetic diseases and neoplastic diseases of hematologic origin, aiding in the diagnosis, prognosis, classification and monitoring of the disease. The aim of this study was to standardize the classical technique in cytogenetics by evaluating the banding G by enzymatic digestion with trypsin and by denaturation with citrate buffer at high temperature, assisting in the karyotype view. In this study we used peripheral blood samples of normal individuals. Cell culture was performed by culturing in situ method, following the method of Moorhead et al. modified (1960). In all cases appropriate metaphases were obtained for analysis and the mitotic index was satisfactory. The results obtained by using different chromosome banding techniques revealed that the G banding by the enzymatic action of the trypsin although considered the gold standard it is more sensitive, cumbersome and it occurs with a larger number of retries due to a variability of the time for degradation of the proteins, requiring rework, this way becoming inefficient in samples with low mitotic index and consequently increasing the cost of the exam. While the banding technique using citrate buffer in high temperature is simple, productive, agile and less expensive